1998
DOI: 10.1002/mds.870130321
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and cerebellar activation in correlation to the action‐induced dystonia in Writer's cramp

Abstract: The pattern of brain perfusion of four patients with writer's cramp and four control subjects were examined using positron emission tomography scans after [(15)O] butanol injections. Each subject was scanned 12 times to cover three repetitions of four different motor tasks with the right hand. Drawing of horizontal lines and variable durations of the writing of a prelearned text were performed in a pseudorandom order, the latter task commencing either simultaneously with or 30 sec or 120 sec before the tracer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 46 publications
6
123
0
Order By: Relevance
“…However, there is increasing evidence for the involvement of the cerebellum in the generation of dystonic movements (Jinnah and Hess 2006;Raike et al 2005). Some dystonia patients have cerebellar structural abnormalities and hypermetabolic signals (Delmaire et al 2007;LeDoux and Brady 2003;Odergren et al 1998;Preibisch et al 2001). In animal models, both the leaner mouse (a Cacna1a mutant) and the Ca v 2.1 null mutant exhibit dystonic movements (Fletcher et al 2001;Green and Sidman 1962).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence for the involvement of the cerebellum in the generation of dystonic movements (Jinnah and Hess 2006;Raike et al 2005). Some dystonia patients have cerebellar structural abnormalities and hypermetabolic signals (Delmaire et al 2007;LeDoux and Brady 2003;Odergren et al 1998;Preibisch et al 2001). In animal models, both the leaner mouse (a Cacna1a mutant) and the Ca v 2.1 null mutant exhibit dystonic movements (Fletcher et al 2001;Green and Sidman 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Both positron emission tomographic and functional magnetic resonance imaging studies implicate the cerebellum in different forms of generalized and segmental dystonias including DYT1 generalized dystonia (Eidelberg et al, 1998), hemidystonia (Ceballos-Baumann et al, 1995), and exercise-induced paroxysmal dystonia (Kluge et al, 1998). Likewise, cerebellar abnormalities are observed in functional imaging studies of focal dystonias, such as writer's cramp (Odergren et al, 1998;Preibisch et al, 2001), cervical dystonia (Galardi et al, 1996), and blepharospasm (Hutchinson et al, 2000). More specifically, increases in cerebellar perfusion or metabolism are consistently observed across functional imaging studies in dystonic patients, regardless of form or etiology.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that a circuit is activated bilaterally in certain types of dystonia that also influence the contralateral side of the body. Odergren et al (1998) observed an increase in blood flow, an alternative index of the cerebral activity, in the hippocampus in writers with writer's cramp using PET. However, there is no report that has described an obvious relationship between dystonia and the hippocampus, although there are many studies that show a relationship between the hippocampus and epilepsy.…”
Section: Regional Changes In [ 14 C]dg Uptake During Dystoniamentioning
confidence: 92%
“…On the other hand, the activity in the hypothalamus, internal globus pallidus, and substanita nigra would be expected to decrease (Vitek 2002). In the chronic type of dystonia, earlier clinical data showed activation on the contralateral side of the primary somatosensory area, striatum, and thalamus by PET (Odergren et al 1998) and functional MRI (Preibisch et al 2001).…”
Section: Regional Changes In [ 14 C]dg Uptake During Dystoniamentioning
confidence: 97%